STUDI PERBANDINGAN PENGGUNAAN CATALYTIC CONVERTER LOGAM ALTERNATIF PADA TINGKAT KEBISINGAN SEPEDA MOTOR EMPAT LANGKAH - Nugraha, Ata Syifa’; Pangestu, Muhammad Tegar Jaya; Ariyanto, Sudirman Rizki (Steam Engineering, 2025)
The growth of motor vehicles in Indonesia, particularly motorcycles, is increasing rapidly. This rise contributes to environmental issues, especially noise pollution, which is caused by the disturbance from vehicle sounds. A catalytic converter, installed in vehicle exhaust systems, reduces harmful emissions but also affects noise levels. This study examines the impact of a nickel-coated copper catalytic converter on motorcycle noise. The research is experimental, comparing the noise produced by a standard exhaust with two experimental exhaust systems fitted with catalytic converters. The study uses a Honda Astrea motorcycle, and noise testing follows the ISO/FDIS 5130 standard. The results are compared to Government Regulation Law No. 07 of 2009, which sets noise limits for motor vehicles. The research results show that the standard exhaust produces a noise level of 83.3 dBA, experiment 1 catalytic converter produces a noise level of 83.6 dBA, and experiment 2 catalytic converter produces a noise level of 82 dBA. From these results, it is evident that experiment 2 catalytic converter succeeded in reducing the noise level by 1.56% compared to the standard exhaust. However, all three types of exhausts still do not meet the quality standards set in the Minister of Environment Regulation No. 07 of 2009 regarding Noise Limits for New Motor Vehicle Types, which sets the maximum noise limit at 80 dBA for stage 1